The Role of Resource Management on MSMEs Financial Performance: Supporting SDG 8 - Decent Work and Economic Growth - Shaferi Intan; Nawarini Alisa Tri; Setyanto Refius Pradipta (E3S Web of Conferences)
This research examines that resource management is an element of MSMEs financial performance, closely tied to achieving sustainable economic growth as outlined in SDG 8. Economic performance is the center of MSMEs' success, and to contribute to the broader goals of decent work and economic growth, entities need to explore and maximize the function of resource management to generate income. Research was conducted on a hundred MSMEs in the Banyumas and Purbalingga areas. Data was collected using questionnaires, and the analytical tool used is SEM-PLS. The research results show that resource management positively affects MSMEs' financial performance. In other words, the support of the internal system within the entity will guide MSMEs to have better income in dynamic economic conditions, thus contributing to the achievement of SDG 8 by promoting sustainable and inclusive growth.